The role of cooling rate on microstructure in a sand-cast Al-Cu–Ag alloy containing high amounts of TiB2. (3rd April 2021) - Ravkov, Lucas; Diak, Bradley; Gallerneault, Mark; Clark, Peter; Marzano, Giuseppe
ABSTRACT: The present work describes the challenges and methodology used to measure transient temperatures during solidification of an Al-Cu–Ag-TiB2 alloy. Transients were measured using multiple thermocouples embedded in four different casting geometries. Solidified microstructures and the related morphologies in the regions surrounding the thermocouple tips were empirically related to the calculated cooling rates. The relation incorporates the grain refiner (TiB2 ) level and an approximation of the alloy-specific growth restriction factor. Results indicate that the measured grain sizes ( d ) of the primary α-Al phase for all sampled material is highly correlated to initial solidification cooling rates ( T ˙ ) ranging from 0.02 to 2.08°C/s as 1 d ( μ m ) ≈ 55.0 ± 9.2 [ 4.5 ] 1 / 3 + 1370 ± 120 85 ⋅ T ˙ 1 / 2 Micro-computed tomography confirms that the primary phase observed using standard metallography solidifies with equiaxed grains in the presence of such thermal gradients.